Clean Grinding Technique: A Facile Synthesis and In Silico Antiviral Activity of Hydrazones, Pyrazoles, and Pyrazines Bearing Thiazole Moiety against SARS-CoV-2 Main Protease (M(pro)) - Abu-Melha, Sraa (Molecules, 2020)
A novel series of some hydrazones bearing thiazole moiety were generated via solvent-drop grinding of thiazole carbohydrazide 2 with various carbonyl compounds. Also, dehydrative-cyclocondensation of 2 with active methylene compounds or anhydrides gave the respective pyarzole or pyrazine derivatives. The structures of the newly synthesized compounds were established based on spectroscopic evidences and their alternative syntheses. Additionally, the anti-viral activity of all the products was tested against SARS-CoV-2 main protease (M(pro)) using molecular docking combined with molecular dynamics simulation (MDS). The average binding affinities of the compounds 3a, 3b, and 3c (−8.1 ± 0.33 kcal/mol, −8.0 ± 0.35 kcal/mol, and −8.2 ± 0.21 kcal/mol, respectively) are better than that of the positive control Nelfinavir (−6.9 ± 0.51 kcal/mol). This shows the possibility of these three compounds to effectively bind to SARS-CoV-2 Mpro and hence, contradict the virus lifecycle.